Production of prototype lab-scale oak barrel analogues using additive manufacturing - Hugh Holds; Kerry Wilkinson; David Jeffery; Frances Jack; Sue Bastian (OENO One)
Experiments involving the maturation of wine or spirits in oak barrels are economically challenging to undertake, especially when there is a need for extensive replication to account for the compositional variability of oak wood. Barrel maturation is also difficult to emulate at a laboratory scale due to the significant increase in surface-area to volume ratio when working with smaller barrel formats. Cost-effective methods that provide a semi-permeable environment for oxygen transfer and modelling of barrel maturation environments while maintaining a more realistic surface to volume ratio would therefore be valuable for researchers.